Advanced solid mechanics : simplified theory - Hejazi, Farzad; Tan, Kar Chun (Boca Raton : CRC Press, 2021)
"The main aim of this book is to demonstrate the fundamental theory of advanced solid mechanics through simplified derivations with details illustrations to deliver the principal concepts. It covers all conceptual principals on two- and three-dimensional stresses, strains, stress-strain relations, theory of elasticity and theory of plasticity in any type of solid materials including anisotropic, orthotropic, homogenous and isotropic. Detailed explanation and clear diagrams and drawings are accompanied with the use of proper jargons and notations to present the ideas and appropriate guide the readers to explore the core of the advanced solid mechanics backed by case studies and examples. Aimed at undergraduate, senior undergraduate students in advanced solid mechanics, solid mechanics, strength of materials, civil/mechanical engineering, this book Provides simplified explanation and detailed derivation of correlation and formula implemented in advanced solid mechanics Covers state of two and three-dimensional stresses and strains in solid materials in various conditions Describes principal constitutive models for various type of materials include of anisotropic, orthotropic, homogenous and isotropic materials. Includes stress-strain relation and theory of elasticity for solid materials. Explores inelastic behaviour of material, theory of plasticity and yielding criteria"--
OCLC-licensed vendor bibliographic record.
Keywords: Mechanics, Analytic; Solids -- Mathematical models; SCIENCE / Mechanics / General; TECHNOLOGY / Engineering / Mechanical